Eccentric cycling is superior to standard rehabilitation for Post-ICU recovery in COVID-19 survivors - María Fernanda Miranda; Cristian Álvarez; Jacob Earp; Álvaro N. Gurovich; Gabriel Nasri Marzuca-Nassr; Luis Peñailillo (PLoS ONE, 2026)
Background The COVID-19 pandemic left numerous patients with post-intensive care syndrome (PICS) that resulted in prolonged physical and health impairment. Compared to standard rehabilitation (STD REHAB), eccentric cycling (ECC) has lower cardiopulmonary demands while inducing greater functional performance improvements after training, which could be ideal for individuals with PICS. Aim To compare the effects of eight weeks of ECC versus STD REHAB on functional performance and quality of life of patients after hospitalization. Methods Randomised crossover design study (clinicaltrial.gov: NCT06895850). Twenty survivors of the COVID-19 infection (50.8 ± 8.8 years old) recruited six months after hospitalization were involved. Participants were initially randomized into ECC (n = 10) or STD REHAB (n = 10). Both groups trained for eight weeks, rested for two weeks, and performed the crossover with the remaining training modality. Exercise time was 20−30 min for ECC and 60 min for STD REHAB. Cardiopulmonary demand was measured during training. Body composition, whole-body manual and handgrip strength, functional performance (6-min walking test; 6MWT, timed up and go; TUG, 1-min sit to stand), cognitive (MoCa and Barthel Index), and quality of life and symptoms (QoL; Patient Health Questionnaire; PHQ and Post-COVID-19 Functional Status Scale; PCFS) were measured before and after interventions. Results Cardiopulmonary demand during training was lesser during STD REHAB than ECC. All variables improved after both interventions, but ECC showed larger improvements in 6MWT, TUG, and Barthel Index compared to STD REHAB. Conclusion Eccentric cycling training induced greater functional and cognitive improvements than standard rehabilitation.